Case report: Brain infarction following percutaneous drainage of a liver abscess post-chemotherapy for pancreatic head cancer - Deng, Wan-qiu; Wei, Bo; Li, Zheng-yan; Liu, Kai (Frontiers in Medicine, 2024)
Bacterial liver abscesses commonly occur in patients with immune deficiencies such as diabetes, post-chemotherapy, or post-immunosuppressive therapy. The recommended treatment for liver abscesses exceeding 5 cm in a diameter is anti-infection therapy combined with percutaneous catheter drainage. Complications may include local spread to adjacent tissues or organs and thrombosis of the liver and portal veins. Rare hematogenous spread to distant sites, such as endophthalmitis and central nervous system embolism, have been reported, though such complications are uncommon post-drainage. This case report details a patient who suffered a brain infarction shortly after percutaneous drainage of a large liver abscess.